The Pattern of Internalization of Aswaja An-Nahdliyah Character Values (Analysis Study of Madrasah Aliyah with Islamic Education Background) - Amin Ary Wibowo; Maragustam Siregar; Mufrod Teguh Mulyo (Publikasi Indonesia, 2022)
Character education in Indonesia continues to be turned on. In various scientific forums, education experts look for new formations, innovations, and reactivation of an educational concept that is characterized by the life of the Indonesian nation. This study aims to determine the characteristics of education in Indonesia. The research used in this research is descriptive qualitative research, namely research that seeks to solve the current problem based on the data, analyze, and interpret the data. This research resulted in the idea of ASWAJA Value-Based Character Education. How to internalize the value of ASWAJA Character Education which is effective and can be part of the formation of a good national personality. ASWAJA-style Islamic education is very relevant and suitable to be reconstructed and socialized to students as a guide for daily religious life.